A short report on NGM282/aldafermin for the treatment of nonalcoholic steatohepatitis (NASH). (3rd October 2021) - Roberts, Stuart K; Majeed, Ammar
ABSTRACT: Introduction: Nonalcoholic fatty liver disease (NAFLD) is rapidly becoming the major cause of liver disease worldwide. Bile acids play a central part in the pathogenesis of NAFLD with agents that target bile acid synthesis and metabolism in development as potential therapies Areas covered: The paper presents an overview of NAFLD and its pathogenesis, with focus on bile acid metabolism and regulation through fibroblast growth factor 19 (FGF-19), and the development of aldafermin as a non-tumorigenic FGF-19 analogue. We explore results from preclinical studies on the efficacy and safety of aldafermin. Expert opinion: Bile acid regulation is a promising therapeutic target in the management of NAFLD. FGF-19 plays key role in this mechanistic pathway, but also exhibits hepatocarcinogenic effect. Aldafermin is an FGF-19 analogue that has shown promising results in nonalcoholic steatohepatitis animal models, with preclinical data supporting its safety profile, specifically, the lack of a tumorigenic effect. The preclinical data presented in this paper support the clinical development of aldafermin, and indeed early data from several phase II clinical trials report promising results in relation to the ability of aldafermin to improve the histological features of NASH particularly in relation to a reduction in liver fat content.